Exosomes Derived from Nerve Stem Cells Loaded with FTY720 Promote the Recovery after Spinal Cord Injury in Rats by PTEN/AKT Signal Pathway - Jianbin Chen; Can Zhang; Shouye Li; Zheming Li; Xiaojing Lai; Qingqing Xia (Journal of Immunology Research)
Background. Spinal cord injury (SCI) remains a challenge owing to limited therapies. The exosome of neural stem cells (NSCs-Exos) and FTY720 transplantation could improve SCI effectively. However, the effect and mechanism of NSCs-Exos combined with FTY720 (FTY720-NSCs-Exos) transplantation in the treatment of SCI are not fully understood. Methods. Sprague Dawley rats (8-week-old) were used to establish the SCI model, followed by the treatment of NSCs-Exos, FTY720, and FTY720-NSCs-Exos. The effect of FTY720, NSCs-Exos, and FTY720-NSCs-Exos combination treatment on hindlimb function, pathological changes, apoptosis activity, and the expression of spinal edema-related proteins and apoptosis-related proteins in SCI models were investigated by BBB scoring, HE staining, TUNEL staining and immunohistochemistry, and Western blotting. Meanwhile, the effect of these treatments on spinal cord microvascular endothelial cells (SCMECs) was detected under hypoxic circumstance. Results. Our results found that FTY720-NSCs-Exos could alleviate pathological alterations and ameliorate the hindlimb function and oxygen insufficiency in model mice after SCI. In addition, exosomes could ameliorate the morphology of neurons, reduce inflammatory infiltration and edema, decrease the expression of Bax and AQP-4, upregulate the expression of claudin-5 and Bcl-2, and inhibit cell apoptosis. At the same time, in vitro experiments showed that FTY720-NSCs-Exos could protect the barrier of SCMECs under hypoxic circumstance, and the mechanism is related to PTEN/AKT pathway. Conclusion. FTY720-NSCs-Exos therapy displayed a positive therapeutic effect on SCI by regulating PTEN/AKT pathway and offered a new therapy for SCI.